Design and characterization of curcumin-loaded electrospun nanofibers based on poly(vinyl alcohol) and sodium alginate - Delia Mihaela Raţă; Anca Niculina Cadinoiu; Luiza Mădălina Grădinaru; Paul Codrin Fuioaga; Gabriela Vochita; Christelle Delaite; Leonard Ionuţ Atanase (eXPRESS Polymer Letters)
Curcumin (CRC) is a natural active principle with important anti-inflammatory, antioxidant, antibacterial, and antitumor properties but has some limitations, such as poor bioavailability, low water solubility, and rapid metabolism. To preserve CRC’s benefits and eliminate its limitations, novel CRC-loaded core-shell electrospun nanofibers were designed. The nanofibers were prepared by co-axial electrospinning method using poly(vinyl alcohol)/CRC as core and poly(vinyl alcohol)/sodium alginate as shell. Polymer coating protects the CRC, increasing its stability. The swelling degree of CRCloaded nanofibers at pH 5.4 was around 326% higher than at pH 7.4 (297%) due to the repulsions of the anion-anion COO–groups. The release efficiency of CRC at pH 7.4 was 81%, while at pH 5.4 was about 96%. In the first 6 h, there was a slower release of CRC from the nanofibers in both acidic and slightly alkaline environments. Nanofibers showed good hemocompatibility, the values being between 2.36–3.22% after the first 90 min of contact, and after 180 min of treatment, the degree of erythrocyte lysis was between 3.78 and 4.93%. Cell viability assay on V79-4 Chinese hamster fibroblasts demonstrated that treatment with free CRC led to a value of 39% whereas for CRC-loaded nanofibers, the cell viability value increased to 59.66%. The results of the present study indicated that CRC-loaded electrospun nanofibers can have great potential for biomedical applications.